The identification and analysis of making-do waste: insights from two Brazilian construction sites - Formoso, Carlos Torres (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2017)
Making-do has been pointed out as an important category of waste in the construction industry. It refers to a situation in which a task starts or continues without having available all the inputs required for its completion, such as materials, machinery, tools, personnel, external conditions, and information. By contrast, the literature points out that improvisation is a ubiquitous human practice even in highly structured business organizations, and plays an important role when rules and methods fail. The aim of this paper is to provide some insights on the nature of making-do as a type of waste, based on two exploratory case studies carried out on construction sites. The main contributions of this research work are concerned with the identification of different categories of making-do and its main causes. This paper also discusses some strategies for reducing making-do on construction sites.